POTENSI TANAH TAILING UNTUK TANAMAN JAGUNG (Zea mays L.) PADA AREAL PERTAMBANGAN RAKYAT DI KECAMATAN RATATOTOK - Edo R. Nangin; Yani E.B. Kamagi; Joice M.J. Supit; Maria Montolalu (Universitas Sam Ratulangi, 2015)
ABSTRACT The research on soil tailing was conducted to know its potency for corn (Zea may L.). It was arranged in descriptive survey descriptive methods and laboratory analysis for soil texture, permeability, total N, available-P and available-K, organic-C and soil pH. Data analysis was done by matching the soil tailing characteristics and the criteria of land suitability for corn. The result showed that the tailing was potencial for corn growth. Keywords: Soil tailing, Soil potency